ID: 65. Issue 1 (November 2015) - Maurer, Barbara; Nivarthi, Harini; Prchal-Murphy, Michaela; Wingelhofer, Bettina; Chen, Doris; Winkler, Susanne; Prochazkova, Jana; Schlederer, Michaela; Pham, Ha; Loizou, Joanna I.; Kenner, Lukas; Sexl, Veronika; et al.
<x xml:space="preserve">Abstract</x> STAT5 transcription factors are essential regulators of differentiation, survival and proliferation during hematopoiesis. Hyperactive STAT5 signaling requires enhanced tyrosine phosphorylation (pYSTAT5), which is found in most hematopoietic cancers and is associated with negative prognosis. Importantly, recurrent gain-of-function STAT5 variants have been detected in different diseases with Peripheral T Cell Lymphoma (PTCL) phenotype. We used cS5F, a hyperactive point mutant of STAT5A (S710F), to generate a mouse model expressing the transgene under the vav-promoter from hematopoietic stem cells (HSC). High pYSTAT5 levels in vav-cS5hi mice led to an aggressive expansion of CD8+ T cells being lethal between 25 and 45 weeks of age. The PTCL-like disease was associated with lymphadenopathy, splenomegaly and T cell infiltrations into various organs. The CD8+ T cells were polyclonal, transplantable and expressed CD25, CD44 and CD62L activation markers. Furthermore, the number of active cycling HSCs increased. The expression profile determined by RNA-seq correlated closely with human PTCL. Our results support the concept that enhanced STAT5 signaling drives PTCL and STAT5 represents a target in these life-threatening malignancies. Therefore, we aim to test the effect of a new STAT5 inhibitor on PTCL cell lines.